ANALISIS KEPUASAN PENGGUNA TERHADAP WEBSITE DINAS PERTANIAN KABUPATEN LOMBOK TENGAH MENGGUNAKAN METODE EUCS - Lestari, Nuri Dinda; Tantoni, Ahmad (LPPM Universitas Sains dan Teknologi Komputer, 2025)
The Agricultural Office of Central Lombok Regency is a government institution that utilizes a website to provide information regarding various agricultural services to the public. This website is used by both the staff of the Agricultural Office and the public. To assess the level of user satisfaction with the website of the Agricultural Office of Central Lombok Regency, this study employs the End User Computing Satisfaction (EUCS) method, which measures satisfaction through five dimensions: Content, Accuracy, Format, Ease of Use, and Timeliness. The purpose of this study is to evaluate the extent of user satisfaction with the website using a Likert scale as the measurement tool. Data were collected through a questionnaire distributed to 55 respondents, consisting of both the staff of the Agricultural Office and the public who use the website. The results show that the level of user satisfaction with the website of the Agricultural Office of Central Lombok Regency falls into the